Crisis management model for Third Sector organizations amid the COVID-19 pandemic - Raptopoulos, M. M. S. C. (2022)
The pandemic caused by COVID-19 impacted people and organizations, including the Third Sector, which has seen greater demand to minimize the social and economic effects generated by the crisis. Based on this issue, the present study aimed to give visibility to the effects and impacts caused by the pandemic, the main actions and strategies adopted by Third Sector organizations and, based on these findings, to propose a crisis management model for the Third Sector. By virtue, qualitative exploratory research of the phenomenological type was carried out, whose data were collected from in-depth interviews and information disclosed on the institutions' websites. Thus, the experiences reported by 32 Brazilian and Portuguese organizations underwent an abductive content analysis, considering the existing theoretical framework and the contents of the interviews. The results showed that none of the organizations was fully prepared to deal with the crisis effects and reacted as situations and events occurred. And, unlike what was reported in previous studies, none of these organizations shut down permanently, financial resources kept on existing, and not all the effects generated by the pandemic meant negative impacts, but opportunities for improvement, as well as breaks in paradigms and learning. The results also showed that adopting good governance levels and agile and flexible management models boosted the organizations’ resilience. Therefore, it was possible to propose a crisis management model to be applied to the Third Sector and to suggest future works and practical and academic applications.